2015
DOI: 10.1016/j.fss.2015.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy data mining and management of interpretable and subjective information

Abstract: Fuzzy set theory offers an important contribution to data mining leading to fuzzy data mining. It enables the management of interpretable and subjective information in both input and output of the data mining process. In this paper, we discuss the notion of interpretability in fuzzy data mining and we present some references on the management of emotions as a particular kind of subjective information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…DM is recognized as an iterative process within which the progress is defined by the discovery of various relationships, through either automatic or manual methods (Lin, Chiu, Huang, & Yen, 2015). DM is a process that is based on the application of machine learning algorithm in a given application task (Marsala & Bouchon-Meunier, 2015). Sparks et al (2016) indicated that machine learning algorithms are the popular DM tools, but require the large training sets to be effective.…”
Section: Overview Of Data Miningmentioning
confidence: 99%
“…DM is recognized as an iterative process within which the progress is defined by the discovery of various relationships, through either automatic or manual methods (Lin, Chiu, Huang, & Yen, 2015). DM is a process that is based on the application of machine learning algorithm in a given application task (Marsala & Bouchon-Meunier, 2015). Sparks et al (2016) indicated that machine learning algorithms are the popular DM tools, but require the large training sets to be effective.…”
Section: Overview Of Data Miningmentioning
confidence: 99%
“…Fuzzy rule-based systems have been applied in various applications, for example in automatic control and robotics [1]- [4], ambient intelligence [5]- [7], computer vision [8]- [10], decision making [11], [12] or data mining [13], [14]. In all of these areas, the proper selection of fuzzy rules is important, especially in control where they determine the stability and quality of the system.…”
Section: Introductionmentioning
confidence: 99%